Brachial and Radial Systolic Blood Pressure Are Not the Same: Evidence to Support the Popeye Phenomenon. Issue 5 (May 2019) - Armstrong, Matthew K.; Schultz, Martin G.; Picone, Dean S.; Black, J. Andrew; Dwyer, Nathan; Roberts-Thomson, Philip; Sharman, James E.
Abstract : Radial intra-arterial blood pressure (BP) is sometimes used as the reference standard for validation of brachial cuff BP devices. Moreover, there is an emerging wearables market seeking to measure BP at the wrist. However, radial systolic BP may differ when compared with brachial; yet some authors have labeled these differences as a fictional Popeye phenomenon. Indeed, differences between brachial and radial systolic BP have never been accurately quantified, and this was the aim of this study. Intra-arterial BP was measured consecutively at the brachial and radial artery in 180 participants undergoing coronary angiography (aged 61±10 years; 69% men). On average, radial systolic BP was 5.5 mm Hg higher than brachial systolic BP. Only 43% of participants had radial systolic BP within ±5 mm Hg of brachial. Additionally, 46%, 19%, and 13% of participants had radial systolic BP >5, between 5 and 10, and between 10 and 15 mm Hg higher than brachial respectively. A further 14% of participants had radial systolic BP >15 mm Hg higher than brachial, representing the so-called Popeye phenomenon. Finally, 11% of participants had radial systolic BP >5 mm Hg lower than brachial. In conclusion, radial systolic BP is not representative of brachial systolic BP, with most participants having a radial systolic BP >5 mm Hg higher than brachial and many with differences >15 mm Hg. Therefore, validation testing of BP devices utilizing intra-arterial BP as the reference standard should use intra-arterial BP measured at the same site as the brachial cuff or wearable device. Abstract : Supplemental Digital Content is available in the text.